Orthodontic-Prosthetic Rehabilitation of Congenital Alveolar Cleft: A case report from infancy to adulthood - Brum, Renata Scheeren; de-Souza, Camila Rodrigues; Ritter, Daltro Enéas; Rocha, Roberto; Volpato, Cláudia Ângela Maziero; Benfatti, César Augusto Magalhães (Journal of Oral Diagnosis, 2021)
Introduction: Cleft lip palate (CLP) treatment is challenging and requires multidisciplinary treatment during patient’s whole life. Aim: To present a case report of a life-time CLP rehabilitation that anatomic features required advanced rehabilitation modalities. Design: A 9-year-old patient was diagnosed as unilateral right CLP. Agenesia and poor prognosis of lateral and central right incisor respectively added complexity to multidisciplinary treatment planning. Results: Orthodontic and surgical procedures performed during infancy and adolescence resulted on satisfactory dental alignment. Anatomical limitations required installation of a hybrid dentogingival implant-supported prosthesis at adulthood. After 3 years of follow-up, implants were osseointegrated and peri-implant tissues were stable, with favorable esthetic and functional outcomes. Conclusions: This challenging case of cleft lip palate, on which tooth with poor prognosis and agenesia were identified, required a multidisciplinary treatment during infancy and adolescence in order to provide adequate conditions for implant placement at adulthood. Implant therapy in complex cases of CLP patients requires advanced treatment modalities, that may include guided bone regeneration, periodontal reconstruction and dentogingival prosthesis.